Impact of patient information leaflets on pain medication intake behavior: a pilot study - Schmitz, Julia (Pain Rep, 2017)
INTRODUCTION: Patient information leaflets on pain medication primarily list side effects while positive effects and action mechanisms remain underrepresented. Nocebo research has shown that negative instructions can lower analgesic effects. OBJECTIVES: Research on information leaflets and their influence on mood, memory of side effects, and intake behavior of healthy participants is needed. METHODS: To determine the ratio of positive to negative phrases, 18 information leaflets of common, over-the-market analgesics were examined of which 1 was selected. In a randomized, controlled study design, 18 healthy participants read this leaflet while 18 control group participants read a matched, neutral leaflet of an electrical device. Collected data concerned the recall of positive and negative contents, mood, anxiety, and the willingness to buy and take the drug. RESULTS: All examined leaflets listed significantly more side effects than positive effects (t(17) = 5.82, P < 0.01). After reading the analgesic leaflet, participants showed a trend towards more negative mood (F(1,34) = 3.78, P = 0.06, η(p)(2) = 0.1), a lower intention to buy [χ(2) (1, n = 36) = 12.5, P < 0.01], a higher unwillingness to take the medication [χ(2) (1, n = 36) = 7.2, P < 0.01], and even a greater recall for side effects than positive effects (t(17) = 7.47, P < 0.01). CONCLUSION: Reading the patient information leaflets can increase fear and lower the intention to buy and the willingness to take a pain medication.